The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fcimb.2020.583418
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Microbiome and Asthma

Abstract: Asthma is a group of inflammatory conditions that compromises the airways of a continuously increasing number of people around the globe. Its complex etiology comprises both genetic and environmental aspects, with the intestinal and lung microbiomes emerging as newly implicated factors that can drive and aggravate asthma. Longitudinal infant cohort studies combined with mechanistic studies in animal models have identified microbial signatures causally associated with subsequent asthma risk. The recent inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 125 publications
0
18
0
1
Order By: Relevance
“…Fungi are suggested to influence intestinal health and disease by suppressing the outgrowth of potential pathobionts, promoting immunoregulatory pathways, and modulating host metabolism ( Huseyin et al, 2017 ; Ni et al, 2017 ; Sam et al, 2017 ; Chin et al, 2020 ). Several clinical studies have identified a distinct fungal microbiota dysbiosis in inflammatory bowel disease (IBD), primary sclerosing cholangitis, asthma, type 2 diabetes mellitus, chronic liver diseases, Parkinson’s disease and other neurological diseases, and even colorectal cancer ( Hoarau et al, 2016 ; Sokol et al, 2017 ; Forbes et al, 2018 ; Coker et al, 2019 ; Cirstea et al, 2020 ; Jayasudha et al, 2020 ; Jiang et al, 2020 ; Lemoinne et al, 2020 ; Qiu et al, 2020 ; van Tilburg Bernardes et al, 2020 ; Ventin-Holmberg et al, 2020 ). Studies of animal models have found that commensal fungi can activate host-protective immune pathways related to epithelial barrier integrity, but can also induce reactions that contribute to events associated with IBD ( Iliev and Cadwell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are suggested to influence intestinal health and disease by suppressing the outgrowth of potential pathobionts, promoting immunoregulatory pathways, and modulating host metabolism ( Huseyin et al, 2017 ; Ni et al, 2017 ; Sam et al, 2017 ; Chin et al, 2020 ). Several clinical studies have identified a distinct fungal microbiota dysbiosis in inflammatory bowel disease (IBD), primary sclerosing cholangitis, asthma, type 2 diabetes mellitus, chronic liver diseases, Parkinson’s disease and other neurological diseases, and even colorectal cancer ( Hoarau et al, 2016 ; Sokol et al, 2017 ; Forbes et al, 2018 ; Coker et al, 2019 ; Cirstea et al, 2020 ; Jayasudha et al, 2020 ; Jiang et al, 2020 ; Lemoinne et al, 2020 ; Qiu et al, 2020 ; van Tilburg Bernardes et al, 2020 ; Ventin-Holmberg et al, 2020 ). Studies of animal models have found that commensal fungi can activate host-protective immune pathways related to epithelial barrier integrity, but can also induce reactions that contribute to events associated with IBD ( Iliev and Cadwell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our immunoblotting results of rAlt a 1 displayed the same characteristics. More importantly, purified Alt a 1 excludes potential complex proteins, including mycotoxins, chitin, mannans, b-1,3-glucans, and endotoxins, which possibly activate a proinflammatory innate response (32). In addition, studies have demonstrated the efficacy of native-like recombinant allergens equal to allergen extracts and purified natural allergens, although they have the same side effects as natural allergens (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Although the urinary microbiome and mycobiome remain relatively unstudied, there is significant evidence indicating that the microbiome and mycobiome of other regions, like the lungs and gut, heavily affect the overall health of the human body [ 10 ]. Evidence has linked lung and gut microbiome and mycobiome health to a host of issues, including asthma, colorectal cancer, alcoholic liver disease, cystic fibrosis, and hypoglycemia [ 10 11 12 13 ]. This type of linkage between microbial health and host health indicates that the urinary microbiome and mycobiome play a similarly important role in the overall health of the human body.…”
Section: Human Genome Microbiome and Mycobiomementioning
confidence: 99%